Bio-based 1, 4-butanediol and tetrahydrofuran synthesis: perspective. Issue 17 (12th August 2022) - Zhu, Yue; Yang, Jiaming; Mei, Feng; Li, Xiaohong; Zhao, Chen
Abstract : Bio-based 1, 4-butanediol and tetrahydrofuran synthesis. Abstract : 1, 4-Butanediol (1, 4-BDO) and tetrahydrofuran (THF) are important feedstocks for the synthesis of polyurethane elastomers, polybutylene succinate (PBS), polybutylene terephthalate (PBT), spandex fibers, special rubbers and special-purpose coatings, as well as universal solvents and important raw materials for organic synthesis. In this review, we will discuss in detail the current new bio-based methods for the synthesis of 1, 4-BDO and THF, including catalytic hydrogenation or bio-conversion of sugars, succinic acid, and furfural to 1, 4-BDO as well as bio-based furfural to obtain THF. The bio-based process for the production of 1, 4-BDO and THF will show continuous competitiveness in the future post-petroleum era. It also provides an outlook on environmentally friendly and energy-efficient low-carbon processes for the green synthesis of 1, 4-BDO and THF in the future post-petroleum era.